Review of Postoperative Delirium in Geriatric Patients After Hip Fracture Treatment. (26th November 2021) - Albanese, Anita M.; Ramazani, Noyan; Greene, Natasha; Bruse, Laura
Introduction: Postoperative delirium (POD) is a serious complication occurring in 4–53.3% of geriatric patients undergoing surgeries for hip fracture. Incidence of hip fractures is projected to grow 11.9% from 258, 000 in 2010 to 289, 000 in 2030 based on 1990 to 2010 data. As prevalence of hip fractures is projected to increase, POD is also anticipated to increase. Signficance: Postoperative delirium remains the most common complication of emergency hip fracture surgery leading to high morbidity and mortality rates despite significant research conducted regarding this topic. This study reviews literature from 1990 to 2021 regarding POD in geriatric hip fracture management. Results: Potentially modifiable and non-modifiable risk factors for developing POD include, but are not limited to, male gender, older age, multiple comorbidities, specific comorbidities (dementia, cognitive impairment, diabetes, vision impairment, and abnormal blood pressure), low BMI, preoperative malnutrition, low albumin, low hematocrit, blunted preoperative cytokines, emergency surgery, time to admission and surgery, preoperative medical treatment, polypharmacy, delirium-inducing medications, fever, anesthesia time, and sedation depth and type. Although the pathophysiology remains unclear, the leading theories suggest neurotransmitter imbalance, inflammation, and electrolyte or metabolic derangements as the underlying cause of POD. POD is associated with increased length of hospital stay, cost, morbidity, and mortality. Prevention and early recognition are key factors in managing POD. Methods to reduce POD include utilizing interdisciplinary teams, educational programs for healthcare professionals, reducing narcotic use, avoiding delirium-inducing medications, and multimodal pain control. Conclusion: While POD is a known complication after hip fracture surgery, further exploration in prevention is needed. Early identification of risk factors is imperative to prevent POD in geriatric patients. Early prevention will enhance delivery of health care both pre- and post-operatively leading to the best possible surgical outcome and better quality of life after hip fracture treatment.